Digital Transformation of Islamic Finance: Educational Program on Islamic Financial Applications for the Millennial Demographic within the Context of the Mujahadah Mosque Pekanbaru - Wali Saputra (Jurnal Ragam Pengabdian, 2025)
The objective of this training initiative is to enhance the digital literacy pertaining to sharia economics among the millennial demographic through the facilitation of both theoretical knowledge and experiential engagement with sharia finance applications. The event transpired at the Mujahadah Rintis Mosque in Pekanbaru, engaging a total of 42 participants drawn from among the student body and the youth affiliated with the mosque. The pedagogical methodologies employed encompassed interactive lectures, practical simulations utilizing applications such as BSI Mobile and LinkAja Sharia, alongside structured group discussions. The outcomes of this endeavor indicated a marked enhancement in the participants' comprehension and proficiency regarding the principles and application of Sharia-compliant financial technology. Quantitative assessments conducted via pre-tests and post-tests revealed an increase in the average score by 29.7 points. The qualitative analysis demonstrated that the participants perceived the training as exceedingly advantageous and fostered the development of a digital community centered around mosque-based sharia economy. This activity illustrates that the approach to digital literacy grounded in sharia finance is efficacious in cultivating a generation of millennials that is both sharia and technology literate.